The use of gammification in the english language classroom to increase vocabulary in beginners (a1 level) - León-Flores, Clara Lucia; Vega-Auquilla, Melita Vanessa (EPISTEME KOINONIA, 2021)
ABSTRACT The present mixed methods study examined the effect of gamification on vocabulary acquisition of software development students enrolled in an A1 English language course at a higher education institute in Cuenca, Ecuador. Study participants were divided into an experimental and control group, with the former receiving instruction through various digital platforms, while the latter were taught through traditional classroom methodologies. After two weeks of instruction, a statistically significant increase was observed in the experimental group's mean vocabulary test scores. It was concluded that student’s vocabulary acquisition and motivation were more positively impacted by gamification than traditional classroom methodologies, thus leading to the conclusion that gamification is an effective and dynamic tool for use in the English language classroom. Recommendations and a sample lesson plan are included.